FcγRIIB inhibits inflammation in a murine model of psoriasis. Issue 2 (November 2022) - Nakabori, Irisu; Hamaguchi, Yasuhito; Sawada, Kaori; Horii, Motoki; Fushida, Natsumi; Kitano, Tasuku; Chenyang, Wang; Xibei, Jia; Ikawa, Yuichi; Komuro, Akito; Matsushita, Takashi
Abstract: Background: Psoriasis is a chronic, inflammatory cutaneous disease. FcγRIIB is a low-affinity receptor for the IgG Fc fragment that provides a negative feedback pathway to down-regulate B-cell antigen receptor signaling. Objective: The aim of this study was to investigate the role of FcγRIIB in the development of murine imiquimod (IMQ)-induced, psoriasis-like skin inflammation. Methods: The experimental psoriasis-like skin inflammation was induced by the topical application of IMQ to the ears of FcγRIIB deficient (FcγRIIB -/- ) and wild-type (WT) mice. After 6 days, epidermal thickness and inflammatory cell infiltration of the skin were histopathologically assessed and cytokine and chemokine expression levels were measured with RT-PCR. Results: Skin inflammation was significantly worse in FcγRIIB -/- mice than WT mice. In the skin, the numbers of Gr-1 + neutrophils, CD11c + dendritic cells, and Foxp3 + T cells were significantly higher in FcγRIIB -/- mice than WT mice. In the spleen, the numbers of CD25 + Foxp3 + T cells and CD19 + IL-10 + B cells were also significantly higher in FcγRIIB -/- mice than WT mice. The mRNA expression of Il-6, Il-17a, and Il-23a was significantly enhanced in FcγRIIB -/- mice. An adoptive transfer of splenic leukocytes from FcγRIIB -/- mice into WT mice also exacerbated skin inflammation compared to WT mice that received splenic leukocytes from WT mice. Intravenous immunoglobulin significantly reduced skin inflammation in WT mice, but this improvement was not observed in FcγRIIB -/- mice. Conclusion: These results indicate that FcγRIIB likely plays a suppressive role in IMQ-induced, psoriasis-like skin inflammation. Furthermore, signal modulation via FcγRIIB is a potential therapeutic target for psoriasis. Highlights: The loss of FcγRIIB exacerbated skin inflammation in imiquimod-induced psoriasis-like skin inflammation. FcγRIIB regulated leukocyte infiltration and cytokine production. Modulating FcγRIIB signaling is a potential therapeutic approach for psoriasis.